Lithuanian School of Photography in the Context of Soviet Ideology About the Doctoral Dissertation ("The sovietization of expression and dissemination of Lithuanian photography" by Margarita Matulytė) - Marija Drėmaitė (Lietuvos Istorijos Studijos)
-